2017
DOI: 10.4103/jcvjs.jcvjs_113_17
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome in unstable Hangman's fracture managed with anterior approach: A prospective study

Abstract: Aim:To study the functional outcome in unstable Hangman s fracture managed with anterior decompression and stabilization with cervical locking plate and tricortical bone graft.Materials and Methods:Between 2010 and 2016, 44 patients (range: 19-75 years) with unstable Hangman's fracture underwent anterior decompression and stabilization with cervical locking plate and tricortical bone graft in our institution.Result:According to the Levine and Edwards classification, all patients were unstable with Type IA 6 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Thus, the potential for surgery to avoid these problems has caused a general shift in literature to use surgery as a primary treatment option rather than deal with conservative treatment that has failed. 12,17,44,49,52 Various radically different surgical techniques may be employed via the anterior, posterior, or combined approach, and their indications, complications, and outcomes must be better understood to guide surgeons as surgical fixation becomes more commonly used in managing unstable hangman's fractures over conservative management. It remains widely accepted that type I fractures may be managed conservatively-only 14 patients of the 627 included in this review who were given a Levine-Edwards classification were type I, as they had excellent union rates nonoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the potential for surgery to avoid these problems has caused a general shift in literature to use surgery as a primary treatment option rather than deal with conservative treatment that has failed. 12,17,44,49,52 Various radically different surgical techniques may be employed via the anterior, posterior, or combined approach, and their indications, complications, and outcomes must be better understood to guide surgeons as surgical fixation becomes more commonly used in managing unstable hangman's fractures over conservative management. It remains widely accepted that type I fractures may be managed conservatively-only 14 patients of the 627 included in this review who were given a Levine-Edwards classification were type I, as they had excellent union rates nonoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Jain et al reported that in 44 patients who underwent ACDF, all had dysphagia that resolved spontaneously within 2 to 3 days. 49 This finding implies that this complication may be far more common than reported as different authors may use different thresholds of duration of dysphagia before reporting it as a complication.…”
Section: Complication Ratesmentioning
confidence: 96%
See 1 more Smart Citation
“…in their series of 44 patients utilized the anterior C2-3 fixation alone, majority being type II with only 3 cases of type III Hangman's fracture. [ 25 ] The unequivocal supremacy of anterior approaches has been well recorded with regards to postoperative pain, neck mobility, and overall satisfaction with neck status in patients treated with the anterior approach. If decompression of the cord and nerve roots is required for neurological recovery, anterior C-3 corpectomy should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…In the postoperative period, dysphagia is a very common complication associated with the anterior approach; however, it usually resolves spontaneously within 2–3 days [14]. Postoperative dysphagia may be due to endotracheal intubation, retraction of the oesophagus, and soft tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%